Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Inses Menurut Undang-Undang Perlidungan Anak Nomor 35 Tahun 2014 - Muhammad Habib albani (Jurnal Perspektif Hukum, 2022)
The son was a gift from the only one god, and child has harkat and dignity to which it is attached as a person whole. The son was of shoots , the potential , young generation to succeed the ideals of the nation's struggle, have a strategic role , as well as having traits and characteristics that ensure the continuity of the life of the nation and state in the future and so that every child is able to carry out responsibilities. Child legal protection is defined as an effort to protect the law against the freedom and human rights of children related to their welfare, including freedom from sexual crimes. From various characteristics incest, a case that occur most frequently is sexual relations are accompanied by violent means, threats of violence, fraud, misdirection and persuade seduced into according to the victim and or powerless which aims to rape and sexually abusing. Setting the legal protection of child victims of criminal acts of incest, as follows: a) the Book Legislation Criminal Law (KUHP), article 285, article 287 and article 294, paragraph (1). b) Act No. 35 of 2014 Concerning amendment to Act No. 23 of 2002 about Child Protection contained in article 26, 59A, 64, 66, 69, 71D.